The Effect of the Educational Game "Edu-Games Bobby Bola" on Cognitive Ability (Using Number Symbols to Count) Children Aged 5-6 Years at Pembina Tanjung Morawa State Kindergarten 2022/2023 Academic Year - Sabrina Putri Aulia Lubis; Kamtini (Indonesian Journal of Advanced Research, 2023)
This research was conducted with the aim of knowing the effect of the educational game "Edu-Games bobby bola" on cognitive abilities (using number symbols to count) of children aged 5-6 years at Pembina Tanjung Morawa Kindergarten. The study population consisted of all children aged 5-6 years, totaling 32 students. The research sample consisted of 16 students who were taken using simple random sampling. Data was collected using the test method, namely the pretest and posttest, and documentation, namely the results of students' cognitive abilities, so on the data were analyzed using the Wilcoxon marked ranking test. The results showed that the educational game "Edu-Games bobby bola" had a significant effect on the cognitive abilities (using number symbols to count) of children aged 5-6 years at Pembina Tanjung Morawa Kindergarten. Based on the findings of this research, it is suggested for teachers to continue working to increase productivity towards new skills and knowledge, especially in implementing the educational game "Edu-Games Bobby Bola".